Acute Effects of Pimobendan on Cardiac Function in Dogs With Tachycardia Induced Dilated Cardiomyopathy: A Randomized, Placebo-Controlled, Crossover Study - Abbott-Johnson, Kaitlin; Pierce, Kursten V.; Roof, Steve; Rio, Carlos L. del; Hamlin, Robert (Frontiers in Veterinary Science, 2021)
Background: Pimobendan provides a significant survival benefit in dogs with cardiac disease, including degenerative mitral valve disease and dilated cardiomyopathy (DCM). Its positive inotropic effect is well-known, however, it has complex effects and the mechanisms behind the survival benefit are not fully characterized. Secondary hemodynamic effects may decrease mitral regurgitation (MR) in DCM, and the benefits of pimobendan may extend to improved cardiac relaxation and improved atrial function. Hypothesis/Objectives: Our objective was to investigate the acute cardiac effects of pimobendan in dogs with a DCM phenotype. We hypothesized that pimobendan would increase left atrial (LA) contractility, reduce mitral regurgitation, improve diastolic function, and lower circulating NT-ProBNP levels. Animals: Seven purpose-bred Beagles were studied from a research colony with tachycardia induced DCM phenotype. Methods: The effects of pimobendan were studied under a placebo-controlled single-blinded cross-over design. In short, dogs underwent baseline and 3 h post-dose examinations 7 days apart with echocardiography and a blood draw. Dogs were randomized to receive oral placebo or 0.25 mg/kg pimobendan after their baseline exam. Investigators were blinded to treatments until all measurements were compiled. Results: When treated with pimobendan, the dogs had significant increases in systolic function and decreases in MR, compared to when treated with placebo. There were no detectable differences in left atrial measures, including LA size, LA emptying fraction, LA functional index or mitral A wave velocity. Heart rate decreased significantly with pimobendan compared to placebo. There was also a decrease in isovolumetric relaxation time normalized to heart rate. NT-proBNP levels had a high degree of variability. Conclusions: Improved mitral regurgitation severity and improved lusitropic function may contribute to the reported survival benefit for dogs with cardiac disease administered pimobendan. Pimobendan did not overtly improve LA function as assessed by echocardiography, and NT-proBNP was not significantly changed with a single dose of this medication. Further studies are needed to better characterize LA effects with other imaging modalities, to better quantify the total improvement of MR severity, and to assess chronic use of pimobendan on diastolic function in DCM.